2010
DOI: 10.1073/pnas.1009785107
|View full text |Cite
|
Sign up to set email alerts
|

Locked nucleic acids (LNAs) reveal sequence requirements and kinetics of Xist RNA localization to the X chromosome

Abstract: A large fraction of the mammalian genome is transcribed into long noncoding RNAs. The RNAs remain largely uncharacterized as the field awaits new technologies to aid functional analysis. Here, we describe a unique use of locked nucleic acids (LNAs) for studying nuclear long noncoding RNA, an RNA subclass that has been less amenable to traditional knockdown techniques. We target LNAs at Xist RNA and show displacement from the X chromosome with fast kinetics. Xist transcript stability is not affected. By targeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
107
4
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(126 citation statements)
references
References 29 publications
12
107
4
1
Order By: Relevance
“…1), previous estimates in differentiating ES cells using the same RT-PCR method with spike-in control of in vitro transcribed RNA suggested 300 transcripts per cell (26). Finally, we investigated the behavior of PRC2 when Xist is acutely displaced from the Xi using the Xist "knock-off" technology (38). We administered to cells a locked nucleic acid (LNA) antisense oligonucleotide (ASO) directed against Xist RNA's Repeat C region (38), the region which binds to YY1 and enables loading of the Xist-PRC2 complex to the Xi nucleation center (8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1), previous estimates in differentiating ES cells using the same RT-PCR method with spike-in control of in vitro transcribed RNA suggested 300 transcripts per cell (26). Finally, we investigated the behavior of PRC2 when Xist is acutely displaced from the Xi using the Xist "knock-off" technology (38). We administered to cells a locked nucleic acid (LNA) antisense oligonucleotide (ASO) directed against Xist RNA's Repeat C region (38), the region which binds to YY1 and enables loading of the Xist-PRC2 complex to the Xi nucleation center (8).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we investigated the behavior of PRC2 when Xist is acutely displaced from the Xi using the Xist "knock-off" technology (38). We administered to cells a locked nucleic acid (LNA) antisense oligonucleotide (ASO) directed against Xist RNA's Repeat C region (38), the region which binds to YY1 and enables loading of the Xist-PRC2 complex to the Xi nucleation center (8). Consistent with previous conventional microscopy (38) and CHARTseq (32), STORM demonstrated that Xist RNA was stripped off of the Xi within 30-60 min of LNA treatment and remained displaced over a 6-8 h time course.…”
Section: Resultsmentioning
confidence: 99%
“…For example, one study reported that targeting the interactions between Xist and chromatin remodeling complexes resulted in the activation of PRC2-regulated genes. 91 However, the practical feasibility of these novel strategies has not been studied in detail for CRC.…”
Section: Tumor Treatmentmentioning
confidence: 99%
“…In addition, the C-repeat PNAs compromise accumulation of Xist RNA on the X chromosome in differentiating female ES cells with an accompanying failure of X-linked gene silencing. A similar effect of locked nucleic acids (LNAs) against the C-repeat was also recently reported [32]. Interestingly, nucleofection of the LNAs against the C-repeat in female embryonic fibroblasts caused a loss of Xist RNA within 1 h, but the effect did not last for long and Xist RNA clouds were reestablished in 8 h. Because there is no change in steady-stated levels of Xist RNA upon LNA treatment, as is the case with PNAs, the antisense LNAs, and also probably PNAs, may displace Xist RNA from the X chromosome.…”
Section: Functional Domains Of Xist Rnamentioning
confidence: 81%